Disseminação da informação nos Websites das instituições do patrimônio público: um enfoque nos arquivos permanentes - Gonçalez, Paula Regina Ventura Amorim [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The wide production of information from Information and Communication Technologies (ICT) has increased the availability of information with the aim at helping the user to understand in general about some knowledge. The Cultural Heritage Institutions – represented by Archives, Libraries and Museums – which are in the Science Information field and other interdisciplinary areas aim at keeping, preserving, organizing and publishing the documental collection, in order to guarantee the access to the information they contain. With the current technologies in the middle of XX century and with the strengthening of these technologies in digital production, from the 80’s in the 20th century, it was possible to change the focus of the document to the information it contains, disseminating it widely in the Web. Thus, nowadays, with the possibilities of access provided by the ICT, the institutions funding documents should make available their documental contents to everybody who needs information. Considering this scenario, this paper aims at analyzing how information from Brazilian States Permanent Archives is available in the Web. The methodology consisted in a theoric investigation based on Information Design and Architecture principles and it was performed in an exploratory level, considering observation of Brazilian State Permanent Archives sites, parameterized by the orientations in the Information Access Law (enacted in 2011 and obligatory in Brazilian territory from November 2012) and by the Guidelines elaborated by CONARQ in 2000 (General Guidelines for the Construction of Websites of Archival Institutions). DaSilva was also used as an instrument of evaluation, as he was the first evaluator of accessibility in Portuguese for Websites... (Complete abstract click electronic access below)

A produção ampliada da informação a partir do uso das Tecnologias de Informação e Comunicação (TIC) proporcionou o aumento da disponibilização da informação com o objetivo de facilitar a compreensão do usuário de maneira geral sobre algum conhecimento. As Instituições do Patrimônio Cultural - representadas pelos Arquivos, pelas Bibliotecas e pelos Museus, presentes nos campos de atuação da Ciência da Informação e áreas afins interdisciplinares - visam à guarda, preservação, organização e divulgação dos acervos documentais, com a finalidade de garantir o acesso à informação neles contida. Destaca-se que com as tecnologias presentes, já na metade do século XX, e com o fortalecimento do uso dessas tecnologias na produção digital, a partir dos anos 80 no século XX, tornou-se possível mudar o enfoque do documento para a informação nele contida, disseminando-a de forma extensiva na Web. Assim, em dias atuais, com as possibilidades de acesso proporcionadas pelas TIC, as instituições custodiadoras de documentos deveriam poder disponibilizar seus conteúdos documentais a todos que necessitem da informação. Diante desse cenário, este trabalho teve como objetivo analisar como a informação dos Arquivos Permanentes dos estados brasileiros está disponibilizada na Web. A metodologia consistiu em uma investigação teórica baseada nos princípios do Design e Arquitetura da Informação e de nível exploratório, a partir de observação dos sites dos Arquivos Permanentes Estaduais Brasileiros, parametrizada pelas orientações constantes na Lei de Acesso à Informação (promulgada em 2011 e cujo cumprimento tornou-se obrigatório no território brasileiro a partir de novembro de 2012) e pelas Diretrizes elaboradas pelo CONARQ em 2000 (Diretrizes Gerais para a Construção de Websites de Instituições Arquivísticas)...
Keywords: Serviços de informação; Arquivos; Web; Tecnologia da informação; Ciência da informação